THE ROLE OF OXIDATIVE STRESS MARKERS IN Β-THALASSEMIC IRAQI PATIENTS INFECTED WITH HEPATITIS C VIRUS DIAGNOSED BY RT-PCR: Life Science-Microbiology - K. AL-ANI, SAHAR; T.S. AL-OUQAILI, DR. MUSHTAK; M. AWAD, DR. MUTHANNA (International Journal of Life Science and Pharma Research, 2019)
Blood transfusion is associated with the risk of infection, especially hepatitis C virus and may lead to peroxidative tissue injury by secondary iron overload in β- thalassemic patients. This study aims to detect HCV-RNA copies in thalassemic patients detected by RT-PCR qualitatively and quantitatively. Also, to measure the role of enzymatic and non-enzymatic anti-oxidants markers in β-thalassemia patients infected with HCV. A total of 200 β-thalassemic patients were collected and analyzed for anti-HCV antibodies using Rapid immunochromatographic assay and enzyme-linked Immunosorbent assay methods. Then, the nucleic acids HCV-RNA of positive samples were extracted by modern automated technique. After that, Amplification for HCV-RNA was amplified. The vitamins C and, E in addition to GSH and GGT were also accurately detected. Out of 100 positive ELISA-anti-HCV antibodies, 72(72%) were also positive for RTPCR considering the assay threshold for the procedure was >13 IU/ ml. The mean viral load in these patients was 545806 ±1009799 IU/ml (1997176 ±3802206) Copies/ml. There was an observed difference (P≤ 0.005) inactivity of TSB, GGT, Protein, Albumin in sera of HCV patients (2.87 ± 1.41, 51.1 ± 60.0 , 6.44 ±2.00 , 3.37 ±0.71) when compared with healthy subjects (0.99 ± 0.46 ; 25.2 ± 12.0 , 7.09 ±0.66 , 3.94 ±0.59) respectively while the Globulin detected evinced no significant difference (P˃ 0.005) in HCV patients (2.90±0.80) as compared with healthy subjects (3.14 ±0.42). Besides there was a significant difference (P≤ 0.005) in serum vitamin C, vitamin E and GSH, between HCV patients groups (57.2 ±46.1, 34.7±14.6, 282.4 ±150.5) and healthy subject groups (73.0 ± 18.0, 44.6 ± 15.6, 353.5± 59.37) respectively. The prevalence of HCV infection was much higher among β-thalassemic patients compared with the healthy blood donors. It is recommended to use nucleic acid based-tests for screening blood donors. The current study shows that there is no correlation between ELISA and viral load in hepatitis C virus infection. On the other hand, Real-Time PCR is a confirmatory diagnostic test and is considered as the golden test for the diagnosis and follow up of hepatitis C virus infection. The HCV infection significantly increases ALT, AST, ALP, GGT, and TSB level above the normal range while vitamins C, E, and GSH decreased considerably.